The role of TP53, APC, and KRAS gene polymorphisms in the development of colorectal cancer - Igor Gavrić; Nenad Lalović; Jovan Kulić (Биомедицинска истраживања, 2025)
This paper discusses about colorectal cancer in correlation with certain genes. Based on the etiological factors, colorectal cancer can be stratified into familial, hereditary, and sporadic. Explorations into hereditary syndromes such as familial adenomatous polyposis and hereditary non-polyposis colorectal carcinoma have unveiled genomic alterations in APC, KRAS, and TP53 genes, which are also implicated in the pathogenesis of sporadic carcinoma. Colorectal cancer constitutes a malignant epithelial neoplasm and ranks among the most prevalent malignancies afflicting both sexes. Despite a persistently elevated mortality rate, the incidence of this carcinoma has exhibited a declining trend over the past decade, though it still represents a substantial public health concern. Advancements in research methodologies have led to the identification of rarer syndromes and their associated genes. Investigation of APC, KRAS, and TP53 genes contributory to the genesis of rare syndromes, in conjunction with previously documented genetic instances, has unveiled the mechanistic underpinnings of carcinogenesis. This has facilitated the development of more precise therapeutic modalities. Despite the notable plethora of newly discovered genetic alterations across various genes, it is imperative to persist in research endeavors to comprehensively elucidate the nature and significance of colorectal carcinoma development processes.
Keywords: colorectal carcinoma; TP53; KRAS; hereditary syndromes; carcinogenesis